2012
DOI: 10.4196/kjpp.2012.16.3.159
|View full text |Cite
|
Sign up to set email alerts
|

Pak1/LIMK1/Cofilin Pathway Contributes to Tumor Migration and Invasion in Human Non-Small Cell Lung Carcinomas and Cell Lines

Abstract: Squamous cell carcinoma (SCC) and adenocarcinoma (AC) are the major histological types of non-small cell lung carcinoma (NSCLC). Although both SCCs and ACs have been characterized histologically and clinically, the precise mechanisms underlying their migration and invasion are not yet known. Here, we address the involvement in NSCLC of the p21-associated kinase1 (Pak1)/LIM kinase1 (LIMK1)/cofilin pathway, which recently has been reported to play a critical role in tumor migration and invasion. The Pak1/LIMK1/c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 35 publications
1
23
0
1
Order By: Relevance
“…Emerging evidences have suggested that PAK1 plays an important role in carcinogenesis and tumor progression . In special, for lung cancer PAK1 could promote cell motility, tumor migration, and invasion through different mechanism . Our current study provided genetic evidence at the population level that PAK1 may be involved in the carcinogenesis and development of lung cancer and further highlighted the important role of genetic variants in PAK1 as molecular biomarkers for lung cancer susceptibility.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Emerging evidences have suggested that PAK1 plays an important role in carcinogenesis and tumor progression . In special, for lung cancer PAK1 could promote cell motility, tumor migration, and invasion through different mechanism . Our current study provided genetic evidence at the population level that PAK1 may be involved in the carcinogenesis and development of lung cancer and further highlighted the important role of genetic variants in PAK1 as molecular biomarkers for lung cancer susceptibility.…”
Section: Discussionsupporting
confidence: 53%
“…Of interest, PAK1 was frequently implicated in the tumorigenesis and up‐regulation of PAK1 was frequently detected in various human cancers including lung cancer . Notably, PAK1 kinase can promote lung cancer cell motility, tumor migration, and invasion through activation of PAK1/LIMK1/cofilin pathway and CRK‐II serine phosphorylation . These evidence collectively revealed the importance of PAK1 in carcinogenesis, especially lung cancer.…”
Section: Introductionmentioning
confidence: 88%
“…Squamous carcinoma cell types are more invasive and migratory compared with adenocarcinoma cells [25]. It has been shown here that nWASP expression correlates with more advanced lung cancer phenotypes and in particular lymph node metastasis.…”
Section: Discussionmentioning
confidence: 79%
“…Cofilin is a member of ADF/cofilin family (Chen et al, 2010), it plays many important parts in apoptosis (Chua et al, 2003;Wang et al, 2008), differentiation (Zhou et al, 2012), invasion and migration (Jang et al, 2012;Popow-Wozniak et al, 2012), tumorigenesis (Polachini et al, 2012). Cofilin was found to translocate to mitochondria after staurosporine-induced apoptosis in neuroblastoma cells (Chua et al, 2003), or oxidantinduced apoptosis in neutrophils (Klamt et al, 2009).…”
Section: Discussionmentioning
confidence: 99%